2008
DOI: 10.1634/stemcells.2007-0898
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Proteoglycans and Microglia Prevent Migration and Integration of Grafted Müller Stem Cells into Degenerating Retina

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 45 publications
2
94
0
1
Order By: Relevance
“…Reactive gliosis represents a barrier to successful stem cell‐based strategies in several neuropathological conditions 4, 5, 13, 37, 38. In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactive gliosis represents a barrier to successful stem cell‐based strategies in several neuropathological conditions 4, 5, 13, 37, 38. In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39. Here, we offer a detailed investigation of retina glial responses to intravitreal BM‐MSC transplantation in order to identify molecular mechanisms behind graft‐induced reactive gliosis in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engrafted cells were shown to express the photoreceptor markers recoverin and rhodopsin, the RGC marker HuD as well as calretinin, which identifies RGCs and amacrine cells (Lawrence et al, 2007). Although integration of undifferentiated Müller stem cells has been observed after subretinal transplantation into adult dystrophic RCS rats, these cells were located in all retinal layers and did not selectively locate to the ganglion cell layer or adopt RGC-like morphology (Singhal et al, 2008).…”
Section: Müller Stem Cells As a Source Of Rgcs For Glaucoma Therapiesmentioning
confidence: 99%
“…Treatment with chondroitinase ABC, for instance, digests chondroitin sulphate proteoglycans and enhances neurite outgrowth in the spinal cord 36 and in the retina. 17,37 Combination treatments that promote migration, neurite growth, and synaptogenesis may be required for the full integration of transplanted cells. Thus, although formidable obstacles remain before cell transplantation will be used clinically to treat inner retinal disease, stepwise progress is leading us closer to protocols that may eventually demonstrate efficacy.…”
Section: Future Directionsmentioning
confidence: 99%